The volume of the solid of revolution is approximately 37439.394 cubic units.
<h3>
How to find the solid of revolution enclosed by two functions</h3>
Let be
and
, whose points of intersection are
,
, respectively. The formula for the solid of revolution generated about the y-axis is:
(1)
Now we proceed to solve the integral: ![f(y) = 6\cdot \ln y](https://tex.z-dn.net/?f=f%28y%29%20%3D%206%5Ccdot%20%5Cln%20y)
(2)
![V = 6\pi \int\limits^{e^{35/6}}_{1} {\ln y} \, dy](https://tex.z-dn.net/?f=V%20%3D%206%5Cpi%20%5Cint%5Climits%5E%7Be%5E%7B35%2F6%7D%7D_%7B1%7D%20%7B%5Cln%20y%7D%20%5C%2C%20dy)
![V = 6\pi \left[(y-1)\cdot \ln y\right]\right|_{1}^{e^{35/6}}](https://tex.z-dn.net/?f=V%20%3D%206%5Cpi%20%5Cleft%5B%28y-1%29%5Ccdot%20%5Cln%20y%5Cright%5D%5Cright%7C_%7B1%7D%5E%7Be%5E%7B35%2F6%7D%7D)
![V = 6\pi \cdot \left[(e^{35/6}-1)\cdot \left(\frac{35}{6} \right)-(1-1)\cdot 0\right]](https://tex.z-dn.net/?f=V%20%3D%206%5Cpi%20%5Ccdot%20%5Cleft%5B%28e%5E%7B35%2F6%7D-1%29%5Ccdot%20%5Cleft%28%5Cfrac%7B35%7D%7B6%7D%20%5Cright%29-%281-1%29%5Ccdot%200%5Cright%5D)
![V = 35\pi\cdot (e^{35/6}-1)](https://tex.z-dn.net/?f=V%20%3D%2035%5Cpi%5Ccdot%20%28e%5E%7B35%2F6%7D-1%29)
![V \approx 37439.392](https://tex.z-dn.net/?f=V%20%5Capprox%2037439.392)
The volume of the solid of revolution is approximately 37439.394 cubic units. ![\blacksquare](https://tex.z-dn.net/?f=%5Cblacksquare)
To learn more on solids of revolution, we kindly invite to check this verified question: brainly.com/question/338504
I got
![- \frac{6 3}{65}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B6%203%7D%7B65%7D%20)
What we know
cos a=-3/5.
sin b=12/13
Angle A interval are between 180 and 270 or third quadrant
Angle B quadrant is between 90 and 180 or second quadrant.
What we need to find
Cos(b)
Cos(a)
What we are going to apply
Sum and Difference Formulas
Basics Sine and Cosines Identies.
1. Let write out the cos(a-b) formula.
![\cos(a - b) = \cos(a) \cos(b) + \sin(a) \sin(b)](https://tex.z-dn.net/?f=%20%5Ccos%28a%20-%20b%29%20%20%3D%20%20%5Ccos%28a%29%20%20%5Ccos%28b%29%20%20%2B%20%20%5Csin%28a%29%20%20%5Csin%28b%29%20)
2. Use the interval it gave us.
According to the given, Angle B must between in second quadrant.
Since sin is opposite/hypotenuse and we are given a sin b=12/13. We. are going to set up an equation using the pythagorean theorem.
.
![{12}^{2} + {y}^{2} = {13}^{2}](https://tex.z-dn.net/?f=%20%7B12%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%20%20%7B13%7D%5E%7B2%7D%20)
![144 + {y}^{2} = 169](https://tex.z-dn.net/?f=144%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%20169)
![25 = {y}^{2}](https://tex.z-dn.net/?f=25%20%3D%20%20%7By%7D%5E%7B2%7D%20)
![y = 5](https://tex.z-dn.net/?f=y%20%3D%205)
so our adjacent side is 5.
Cosine is adjacent/hypotenuse so our cos b=5/13.
Using the interval it gave us, Angle a must be in the third quadrant. Since cos is adjacent/hypotenuse and we are given cos a=-3/5. We are going to set up an equation using pythagorean theorem,
.
![( - 3) {}^{2} + {x}^{2} = {5}^{2}](https://tex.z-dn.net/?f=%28%20-%203%29%20%7B%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%20%20%7B5%7D%5E%7B2%7D%20)
![9 + {x}^{2} = 25](https://tex.z-dn.net/?f=9%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%2025)
![{x}^{2} = 16](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%3D%2016)
![x = 4](https://tex.z-dn.net/?f=x%20%3D%204)
so our opposite side is 4. sin =Opposite/Hypotenuse so our sin a =4/5.Sin is negative in the third quadrant so
sin a =-4/5.
Now use cosine difference formula
![- \frac{3}{5} \times \frac{5}{13} + - \frac {4}{5} \times \frac{12}{13}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B3%7D%7B5%7D%20%20%5Ctimes%20%20%5Cfrac%7B5%7D%7B13%7D%20%20%2B%20%20%20-%20%5Cfrac%20%7B4%7D%7B5%7D%20%20%5Ctimes%20%20%5Cfrac%7B12%7D%7B13%7D%20)
![- \frac{15}{65} + ( - \frac{48}{65} )](https://tex.z-dn.net/?f=%20%20-%20%5Cfrac%7B15%7D%7B65%7D%20%2B%20%28%20%20-%20%5Cfrac%7B48%7D%7B65%7D%20%20%29)
![- \frac{63}{65}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B63%7D%7B65%7D%20)
Hope this helps
Answer:
Since C is the mid point,
therefore, (6x - 4)/2 = 4x-3
=> 6x - 4 = 2X(4x-3) = 8x - 6
=> 6x - 8x = -6 + 4
=> -2x = -2
=> x = (-2)/(-2) = 1
Hence, CD = AC = 4x - 3 = 4X1 - 3 = 1
Step-by-step explanation:
1) Subtract 1,000 from 16,000.
Now you have 15,000.
2) Divide 15,000 by 3.
The original price of the car was $5,000.
Our system of equations is:
y = -3x + 9
y = -x - 5
To solve this system of equations, we are going to use substitution. This means that we are going to substitute the second equation into the first equation since both are already solved for y in terms of x.
y = -3x + 9
-x - 5 = -3x + 9
Now, we must simplify by moving all of the constant terms to one side of the equation and all of the variable terms to the other side.
-x - 5 = -3x + 9
2x - 5 = 9
2x = 14
Finally, to undo the multiplication between the coefficient 2 and the variable x, we must divide both sides by 2 to get the variable x alone.
x = 7
Next, we must substitute in this value we have solved for x into one of the original equations to solve for the other variable, y.
y = -3x + 9
y = -3(7) + 9
To simplify, we must multiply through the parentheses and combine like terms by addition.
y = -21 + 9
y = -12
Therefore, your final answer is x = 7 and y = -12, or as an ordered pair (7, -12).
Hope this helps!